Risk Factors for Early Recurrence of Gallstones in Patients Undergoing Laparoscopy Combined With Choledochoscopic Lithotomy: A Single-Center Prospective Study - Wang, Bo; Huang, Anhua; Jiang, Min; Li, Haidong; Bao, Wenqing; Ding, Kan; Jiang, Zhaoyan; Zhao, Gang; Hu, Hai (Frontiers in Surgery, 2021)
Objective: For patients with gallstones, laparoscopy combined with choledochoscopic lithotomy is a therapeutic surgical option for preservation rather than removal of the gallbladder. However, postoperative recurrence of gallstones is a key concern for both patients and surgeons. This prospective study was performed to investigate the risk factors for early postoperative recurrence of gallstones. Methods: The clinical data of 466 patients were collected. Each patient was followed up for up to 2 years. The first follow-up visit occurred 4 months after the operation, and a follow-up visit was carried out every 6 months thereafter. The main goal of each visit was to confirm the presence or absence of gallbladder stones. Factors associated with gallstone recurrence were analyzed by univariate analysis and Cox regression. Results: In total, 466 eligible patients were included in the study, and 438 patients (180 male, and 258 female) completed the 2-year postoperative follow-up. The follow-up rate was 94.0%. Recurrence of gallstones was detected in 5.71% (25/438) of the patients. Univariate analysis revealed five risk factors for the recurrence of gallstones. Multivariate Cox regression analysis showed that multiple gallstones, a gallbladder wall thickness of ≥4 mm, and a family history of gallbladder stones were the three predictive factors for postoperative recurrence of gallstones (P < 0.05). Conclusion: The overall 2-year recurrence rate of gallstones after the operation was 5.71%. Multiple gallstones, a gallbladder wall thickness of ≥4 mm, and a family history of gallstones were the three risk factors associated with early postoperative recurrence of gallstones.